Digital Business Communities in EU - Шейко, І. А.; Помогалова, Н. В.; Полозов, О. Б. (ХНУРЕ, 2022)
Digital business communities allow you to quickly find partners, suppliers, agents, and expand your network of contacts and have some advantages.
Keywords: digital business communities; european business communities; manufacturing partnership; business innovation